Regulatory focus and burnout in nurses: The mediating effect of perception of transformational leadership. Issue 6 (14th April 2014) - Shi, Rui; Zhang, Shilei; Xu, Hang; Liu, Xufeng; Miao, Danmin
Abstract : This correlation study investigated the relationship between nurses' regulatory focus and burnout, as mediated by their perceptions of transformational leadership, using a cross‐sectional research design with anonymous questionnaires. In July–August 2012, data were collected from 378 nurses from three hospitals in Shaanxi Province, China, using self‐report questionnaires for measuring the nurses' regulatory focus, their level of burnout and their perception of whether the leadership of their supervisor was transformational. Structural equation modelling and bootstrapping procedures were used to identify the mediating effect of their perceptions of transformational leadership. The results supported our hypothesized model. The type of regulatory focus emerged as a significant predictor of burnout. Having a perception of transformational leadership partially mediated the relationship between regulatory focus and burnout. Having a promotion focus reduced burnout when the participants perceived transformational leadership, whereas having a prevention focus exhibited the opposite pattern. The mediating effect of the perception of transformational leadership suggests that a promotion focus may help diminish burnout, directly and indirectly. Nurse managers must be aware of the role of a regulatory focus and cultivate promotion focus in their followers.